On the history of elastohydrodynamics: The dramatic destiny of Alexander Mohrenstein‐Ertel and his contribution to the theory and practice of lubrication. Issue 7 (9th April 2014) - Popova, E.; Popov, V.L.
<x xml:space="preserve">Abstract</x> The paper is devoted to the life and work of Alexander Mikhailovich Ertel, the founder of elastohydrodynamics. He was the first to solve problems of hydrodynamic lubrication accounting for effects of elastic deformation of the bodies in contact as well as for the dependence of the viscosity of the lubricant on pressure and temperature, thereby opening a new branch of tribology – elastohydrodynamics. However, due to complicated historical entanglements, the real authorship remained unknown over many years.